Peran Work-Life Integration Terhadap Organizational Commitment Pada Karyawan Generasi Z - Valerie Alicia Erica Rumbajan; Zamralita; Jessica Chandika (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2026)
Background: Generation Z employees in Indonesia face dynamic demands from both work and personal life, making work-life integration (WLI) a critical issue. WLI emphasizes the blending of work and personal roles, while organizational commitment (OC) reflects employees’ attachment and loyalty to the organization. Understanding how WLI influences OC is essential in the current context of flexible work arrangements. Objective: This study aims to investigate and analyze the role of work-life integration in influencing organizational commitment among Generation Z employees in Indonesia. Method: A quantitative non-experimental approach with purposive sampling was employed, involving 211 employees from various industries. Data were collected using WLI scales and OC questionnaires, then analyzed using simple linear regression and difference tests to examine both the overall effect and dimensions of OC. Result: The findings show that WLI and OC levels are moderate. Regression analysis indicates that WLI does not significantly affect OC, either overall or within affective, continuance, and normative commitment dimensions. Difference tests reveal significant variations in WLI based on work system, while other demographic characteristics have no significant effect. Conclusion: Although Generation Z employees exhibit moderate levels of WLI and OC, these variables do not have a significant relationship, suggesting that other factors beyond WLI may influence organizational commitment.